High-Performance Removal Of Acids And Furans From Wheat Straw Pretreatment Liquid By Diananofiltration - Mohd Shafiq, Mohd Sueb; Jakub , Zdarta; Teofil , Jesionowsk; Gunnar , Jonsson; Anne , S. Meyer; Henning , Jørgensen; Manuel , Pinelo (Taylor, 2017)
Two model solutions and a real stream from the hydrothermal pretreatment of wheat straw were subjected to nanofiltration, and permeate flux, retention and resistance to fouling were evaluated. Three commercial NF membranes were tested, and a pressure of 4 bars (range: 1–20 bars) and a temperature of 20ºC (range: 20–50ºC) were found to provide the best results in terms of retention. A subsequent nanodiafiltration consisting of five cycles enabled one to recover 90% of the monosaccharides (purity >99%). This result showed that diananofiltration could be a promising strategy for the recovery of high-purity streams of monosaccharides from pretreatment liquids.